KERAGAMAN LUMUT DI RESORT KARANG RANJANG, TAMAN NASIONAL UJUNG KULON, BANTEN - Windadri, Florentina Indah (Jurnal Teknologi Lingkungan, 2009)
Karang Ranjang resort is a part of Ujung Kulon National Park at Banten Province. Ithas two type ecosystem of forest. The coastal forest ecosystem are dominated byPandanaceae Plant and the lowland forest ecosystem is dominated by Arecaceae.Floor of the lowland forest always covered by sea water when flooding.The first bryophyte research in this park was been done by surrounding methodeand it recorded 50 specimen numbers of mosses. The identification result of the48 speciment numbers found 33 species. Mniomalia semilimbata is dominant specieson the research areas. Two species of the mosses have endemic status, Fissidensteysmanianum as endemic species in Java and Calymperes cougiense foundabundant in the Malesia region and endemic in Polynesia